2013
DOI: 10.3109/09638288.2012.748837
|View full text |Cite
|
Sign up to set email alerts
|

A fast-moving target in the Valpar assembly task improved unimanual and bimanual movements in patients with schizophrenia

Abstract: A fast-moving target might elicit faster, smoother, and more synchronized movements than might a slow-moving target during a bimanual assembly task for patients with mild schizophrenia. The findings of impaired movement kinematics under the slow-target condition suggest that patients with schizophrenia need movement training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Indeed, earlier research has anticipated lower reliability of mechanical instruments for measuring facial movement problems than hand ones (18). The motion capture system was more sensitive to detecting differences in bradykinesia and dyskinesia between patients and healthy people than the clinical rating scales, which is consistent with earlier evidence that hand instrumental measures are more sensitive than rating scales (12,15,16,19,25,26). This study further showed that the motion capture system was also more sensitive than the rating scales in terms of detecting differences in facial bradykinesia and dyskinesia between patients and healthy people.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Indeed, earlier research has anticipated lower reliability of mechanical instruments for measuring facial movement problems than hand ones (18). The motion capture system was more sensitive to detecting differences in bradykinesia and dyskinesia between patients and healthy people than the clinical rating scales, which is consistent with earlier evidence that hand instrumental measures are more sensitive than rating scales (12,15,16,19,25,26). This study further showed that the motion capture system was also more sensitive than the rating scales in terms of detecting differences in facial bradykinesia and dyskinesia between patients and healthy people.…”
Section: Discussionsupporting
confidence: 82%
“…Two reflective markers were placed on the ulnar styloid process (representing the wrist) and the thumbnail of the right hand and additional two markers on the object (Figure 2). This right-hand task was adapted based on the tasks in previous studies that detected movement abnormalities in schizophrenia patients (25)(26)(27).…”
Section: The Right-hand Taskmentioning
confidence: 99%
See 3 more Smart Citations